The Origin of Unpleasant Aftertastes in Synthetic Sweeteners: A Hypothesis - Acevedo, Waldo; Temussi, Piero A. (Frontiers in Molecular Biosciences, 2019)
Most sweeteners are plagued with unwanted unpleasant aftertastes. Here we examined the possibility that one of the main reasons for this is the similarity of sweet and umami receptors. We performed docking calculations on models of sweet and umami receptors using as template the recently determined solid state structure of the first taste receptor, the medaka fish T1R2-T1R3 receptor. Our results show convincingly that sweeteners can be recognized also by the T1R1-T1R3 umami receptor, owing to the similarity of its architecture to that of the sweet receptor. We hypothesize that the T1R1-T1R3 receptor plays a key role in modulating the quality of sweet tastants, hinting at a simple explanation of their aftertaste. The prevailing ideas on taste coding favor strict labeling of taste cells, which would exclude that umami receptors can recognize other taste sensations. If some cross-talk based on the combinatorial model of taste is accepted, some sweet ligands can exert a bitter sensation. However, even if cross-talk is not admitted, direct stimulation of the umami receptor is bound to cause an aftertaste incompatible with good sweet quality.